A novel cyanoacrylate-based matrix excipient in HPMCP capsules forms a sustained intestinal delivery system for orally administered drugs with enhanced absorption efficiency. Issue 5 (14th January 2021) - Song, Liya; Chen, Pengfei; Yu, Jin; Han, Xiaolu; Hua, Yabing; Liu, Shan; Pang, Bo; Gao, Jing; Ma, Jiahua; Xu, Liang
Abstract : ASA–polyMECA–HPMCP could improve drug bioavailability. Abstract : Patients prefer oral drug delivery due to its convenience and noninvasiveness. Nevertheless, a multitude of potentially clinically important drugs will not reach the market or achieve their full potential, due to their low bioavailability and instability in gastric acid. In this study, a novel oral drug delivery system based on poly-cyanoacrylate [a polymer of 2-(2-methoxyethoxy)ethyl-2-cyanoacrylate (MECA)] and hydroxypropyl methylcellulose phthalate (HPMCP) was developed and shown to permit intestinal targeting and sustained drug release. Aspirin [acetylsalicylic acid (ASA)] was selected as a model drug for atherosclerosis treatment. It was physically dissolved in liquid MECA, and the ASA–MECA matrix was then polymerized into a solid drug-loading depot in an HPMCP shell. The delivery of the drug depot in the intestine was achieved with the HPMCP shell; then the polymerized MECA (polyMECA) provided sustained drug release. The polyMECA excipient was not absorbed by the intestine due to its high molecular weight; a fluorescein-labeled assay indicated that it was excreted completely in feces after drug release. The formulation, ASA–polyMECA–HPMCP, showed good intestinal targeting and sustained drug release in vitro and in vivo . Pharmacokinetic studies indicated that this formulation improved the bioavailability of ASA relative to commercially available controls. ASA–polyMECA–HPMCP showed desirable anti-atherosclerosis efficacy in a rabbit model, with significant enhancement of atheromatous lesion stability. Biosafety tests proved the low toxicity of ASA–polyMECA–HPMCP and the polyMECA matrix. We believe that this work has provided a practical and biocompatible system for sustained intestinal drug delivery that can be applied broadly with various drugs for specific therapeutic aims.